Copy Number Variation Pattern for Discriminating MACROD2 States of Colorectal Cancer Subtypes - Zhang, ShiQi; Pan, XiaoYong; Zeng, Tao; Guo, Wei; Gan, Zijun; Zhang, Yu-Hang; Chen, Lei; Zhang, YunHua; Huang, Tao; Cai, Yu-Dong (Frontiers in Bioengineering and Biotechnology, 2019)
Copy number variation (CNV) is a common structural variation pattern of DNA, and it features a higher mutation rate than single-nucleotide polymorphisms (SNPs) and affects a larger fragment of genomes. CNV is related with the genesis of complex diseases and can thus be used as a strategy to identify novel cancer-predisposing markers or mechanisms. In particular, the frequent deletions of mono-ADP-ribosylhydrolase 2 (MACROD2) locus in human colorectal cancer alters DNA repair and the sensitivity to DNA damage and results in chromosomal instability. The relationship between CNV and cancer has not been explained. In this study, on the basis of the genome variation profiling by the SNP array from 651 colorectal cancer (CRC) primary tumors, we computationally analyzed the CNV data to select crucial SNP sites with the most relevance to three different states of MACROD2 (heterozygous deletion, homozygous deletion, and normal state), suggesting that these CNVs may play functional roles in CRC tumorigenesis. Our study can shed new insights into the genesis of cancer based on CNV, providing reference for clinical diagnosis and treatment prognosis of CRC.